2022
DOI: 10.3390/ijms231911488
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Mitochondria Dysfunction in Dyslipidemic Mice

Abstract: Dyslipidemia triggers many severe pathologies, including atherosclerosis and chronic inflammation. Several lines of evidence, including our studies, have suggested direct effects of dyslipidemia on cardiac energy metabolism, but details of these effects are not clear. This study aimed to investigate how mild dyslipidemia affects cardiac mitochondria function and vascular nucleotide metabolism. The analyses were performed in 3- and 6-month-old knock-out mice for low-density lipoprotein receptor (Ldlr−/−) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…34 Mitochondrial function is highly regulated by the mitochondrial outer membrane potential ( Ψ m ) and it plays an important role in mitochondrial biogenesis and metabolism. 35–37 Pretreatment of MitoEGCG 4 and MitoEGCG 6 attenuated the loss of Ψ m induced by H 2 O 2 treatment in H9c2 cells in comparison to EGCG. It was also observed that EGCG was reducing the Ψ m of cells at concentrations above 50 μM and therefore acting as a pro-oxidant to cardiomyocyte cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…34 Mitochondrial function is highly regulated by the mitochondrial outer membrane potential ( Ψ m ) and it plays an important role in mitochondrial biogenesis and metabolism. 35–37 Pretreatment of MitoEGCG 4 and MitoEGCG 6 attenuated the loss of Ψ m induced by H 2 O 2 treatment in H9c2 cells in comparison to EGCG. It was also observed that EGCG was reducing the Ψ m of cells at concentrations above 50 μM and therefore acting as a pro-oxidant to cardiomyocyte cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The electron flow assay was performed as described previously [54]. Briefly, isolated mitochondria from a rat's heart were suspended in a mitochondrial assay solution (MAS, 1×), which contained 70 mM sucrose, 220 mM mannitol, 10 mM KH 2 PO 4 , 1 mM ethylene glycol-bis(β-aminoethyl ether)-N,N,N ,N -tetraacetic acid tetrasodium salt (EGTA), 5 mM MgCl 2 , 2 mM 4-(2-Hydroxyethyl)piperazine-1-ethanesulfonic acid sodium salt, N-(2-Hydroxyethyl)piperazine-N -(2-ethanesulfonic acid) sodium salt (HEPES), and 0.2 % (w/v) albumin bovine serum (BSA), pH 7.2.…”
Section: Mitochondrial Respiration Analysismentioning
confidence: 99%
“…Murine in vivo or cellular models are useful for studying atherosclerosis ethology, pathogenesis, and complications, providing a valuable platform for testing different pharmacological approaches ( Lee et al, 2017 ). Recently, we have documented an impairment in cardiac mitochondria function in mouse model of human-like dyslipidemia ( Braczko et al, 2022 ). The aim of this work was to investigate the pleiotropic effects of statins and PCSK9i on mitochondrial and cellular function of cardiac endothelial cells and cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%